Formulation, Standardization, and in Vitro Pharmacological Assessment of a Polyherbal Blend for the Management of Type 2 Diabetes and Protection against Cisplatin-Induced Nephrotoxicity - Shelke, Priyanka Arvind; Chatla, Supriya; Gavaroji, Shankar; Mohapatra, Rashmi; Pathak, Ashutosh; Waghmare, Nilkamal; Armo, Rohini; Varad, Yeolekar (Journal of Neonatal Surgery, 2025)
The present study focuses on the development and pharmacological evaluation of a novel herbal formulation (RG-PV-HF) for its antidiabetic and nephroprotective potential in in vitro models. The extract was prepared using the cold maceration method and subjected to phytochemical screening, confirming the presence of flavonoids, tannins, phenols, saponins, alkaloids, and glycosides. The total phenolic content was determined using the Folin-Ciocalteu method, yielding 317.87 mg GAE/g extract. The extract exhibited α-amylase and α-glucosidase inhibition in a concentration-dependent manner, with IC₅₀ values of 592.88 µg/mL and 321.77 µg/mL, respectively. Additionally, DPP-4 inhibition was observed, suggesting a role in incretin-based glucose regulation. The cytotoxicity assessment using the MTT assay on HEK-293 cells demonstrated high cell viability, confirming its biocompatibility. Furthermore, RG-PV-HF provided significant protection against cisplatin-induced nephrotoxicity, highlighting its potential antioxidant and nephroprotective effects. The findings suggest that RG-PV-HF could be a promising natural therapeutic candidate for managing Type 2 diabetes and nephrotoxicity, warranting further investigation into its mechanism of action and in vivo efficacy